Pengaruh Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian iPhone Melalui Minat Beli Pada Mahasiswa di Kota Padang - Muhammad Agung Zamzam; Vicky Brama Kumbara; Della Asmaria Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to determine the effect of product quality and brand image on purchasing decisions through purchase intention as an intervening variable. The independent variables in this study are product quality and brand image, while the dependent variable is purchasing decision. There were 100 respondents as the research sample. Data were obtained from iPhone users among students in Padang City, with data analysis using SmartPLS 4.0. The results of this study indicate that product quality has a positive and significant effect on purchase intention, brand image has a positive and significant effect on purchase intention, product quality has a positive and significant effect on purchase decisions, brand image has a positive but insignificant effect on purchase decisions, purchase intention has a positive and significant effect on purchase decisions, product quality has a positive and significant effect on iPhone purchase decisions through purchase intention as an intervening variable, and brand image has a positive but insignificant effect on iPhone purchase decisions through purchase intention as an intervening variable